Medical Leadership and Management A Case-based Approach - MacCarrick, Geraldine (Springer London : Imprint: Springer, 2014)
Using a case-based approach, Medical Leadership and Management uses internationally recognized competency frameworks to support knowledge acquisition and skills relevant to medical management and leadership. The text and supporting cases studies describe key medical management and leadership competencies, illustrating the theoretical and practical aspects of these competencies in the healthcare setting.   With 23 years in clinical, teaching and health administration, Dr Geraldine MacCarrick has extensive knowledge of the education and training issues facing the medical profession.   Despite lack of formal training, doctors worldwide are increasingly assuming greater leadership and management roles in healthcare. Effective medical leadership is recognized as essential for improving the performance of health services, enhancing the wellbeing of patients and the quality of outcomes.   Medical Leadership and Management is of interest to all medical educators interested in supporting their students to acquire leadership and management skills in preparation for graduation and beyond.